Krisis Komunikasi Publik dan Social License to Operate: Analisis Konseptual Unjuk Rasa Masyarakat Kabupaten Pati Tahun 2025 - Salma Asriani; Vivin Deva Alia; Marjam Desma Rahadhini (Jurnal of Management and Social Sciences, 2026)
This study is motivated by the escalation of mass protests in Pati Regency throughout 2025, triggered by significant increases in Land and Building Tax (PBB-P2) rates and prolonged agrarian disputes in the Kendeng Mountains region. These socio-political tensions indicate weaknesses in public communication governance between local government authorities and local communities. This conceptual article employs an integrative literature review combined with a descriptive-analytical approach to secondary data derived from media transcripts, fiscal policy documents, and legal studies on public order management. The findings reveal that the protests were fundamentally driven by a public communication crisis rather than merely fiscal or agrarian policy issues. The implementation of coercive one-way communication and confrontational rhetoric by government elites undermined relational trust and threatened the communal dignity of citizens. Furthermore, post-crisis apology strategies were perceived as insufficiently authentic when not accompanied by substantive corrective actions. The study concludes that the formal legal validity of local regulations does not guarantee successful implementation without obtaining a community's Social License to Operate (SLO). Therefore, this article proposes the Symmetrical Community Engagement (SCE) framework as a new paradigm for repositioning public sector public relations toward a proactive and participatory approach from the pre-legislative stage to support democratic governance